STRATEGI PEMENANGAN YAN ANTON FERDIAN DI PILKADA LANGSUNG KABUPATEN BANYUASIN 2013 - Indah Kartika Ratri; Amaliatulwalidain Amaliatulwalidain; Isabella Isabella (UNIVERSITAS INDO GLOBAL MANDIRI, 2019)
Banyuasin regency on 6 Juni 2013, held direct election to choose candidate for regent and vice regent in the period 2013-2018. In this local election an interesting to study because one candidate of regent is a son of the previous regent Amiruddin Inoed. The candidate is Yan Anton Ferdian. In the end Yan Anton Ferdian won on Banyuasin local election. The purpose of this study is to reseach about strategies are applied by Yan anton Ferdian to win local election in Banyuasin 2013. Theories and consepts used in answering research questions using political strategy, theory of the social capital of piere bourdiue and voter behaviour. While the method in this reseach, using qualitatif analytical reseach method using primary data types, with descriptive methodelogy. From the reseach, it was found that the winning of Yan Anton Ferdian come from the power of sosial capital by his father, who bought on behavior of voters to choose Yan Anton Ferdian In Banyuasin election 2013.Keywords: Local election, Sosial Capital , and Voter Behavior